(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2017)
The old adage states that humankind moves “one step forward” before it moves “two steps backward”, suggesting that there is no such thing as a linear evolution. This is particularly true when applied to our present time, the “age of globalization”. In the case of globalism, “two steps back” are needed in order to assess more soberly the present historical trajectory, and capture the “internal dialectic” of globalism. In fact, what we are witnessing today in many parts of the world is a backlash to globalism, manifest in an upsurge of traditional nationalism, if not chauvinism and ethnocentrism. The core issue is a difficult relation between nearness and distance, between the concretely singular and the general/universal which the term “globalism” seeks to capture but, of course, cannot explain. My reflections in the following seek to explore and shed some light on this relation. In a first step, I venture into philosophical (and theological) terrain in an effort to discern the meaning of human situatedness in a place, a space, or a “world”. Next, I discuss the inevitable tensions or conflicts between nearness and distance, that is, the inner “dialectic” between the local and the global. Finally, I translate the local/global syndrome into the correlation of “earth and world”, “roots and routes”, familiar loyalties and unfamiliar peregrinations.